Antimicrobial Activity Test of Anti-Acne Cream Containing Sodium Ascorbyl Phosphate Against Staphylococcus Epidermidis Under Storage Conditions - Mau’ulhayat Nurulah; Herman Widjaja (PROMOTOR, 2026)
Sodium Ascorbyl Phosphate is a derivative of vitamin C used as an active ingredient in anti-acne creams. According to the literature,the concentration of Sodium Ascorbyl Phosphate used in anti-acne creams ranges from 0.5% to 5%. The maximum concentration considered effective for treating acne is 5%. The evaluation was conducted on physical parameters including organoleptic properties, homogeneity, viscosity, and pH under storage conditions at room temperature (20°C–30°C) and warm temperature (30°C–40°C) for four weeks. Antimicrobial activity testing was carried out using the cylinder diffusion method. The results of the antimicrobial activity test showed that the higher the concentration of Sodium Ascorbyl Phosphate, the greater the inhibitory effect on the growth of Staphylococcus epidermidis. The study demonstrated that an increase in Sodium Ascorbyl Phosphate concentration is directly proportional to the increase in inhibitory activity against Staphylococcus epidermidis growth. Storage at room temperature showed better physical stability and antimicrobial activity compared to storage at warm temperature. Therefore, Sodium Ascorbyl Phosphate is proven to be effective as an active ingredient in anti-acne cream formulations.